Replanting the Birthing Trees: A Call to Transform Intergenerational Trauma into Cycles of Healing and Nurturing - Catherine Chamberlain; Jacynta Krakouer; Paul Gray; Madeleine Lyon; Shakira Onwuka; Ee Pin Chang; Lesley Nelson; Valda Duffield; Janine Mohamed; Shaydeen Stocker; Yalmay Yunupingu; Sally Maymuru; et al. (Genealogy)
Aboriginal and Torres Strait Islander ways of knowing, being and doing have fostered physical, social, and emotional wellbeing for millenia, forming a foundation of strength and resilience. However, colonisation, systemic violence and discrimination—including the forced removal of Aboriginal and Torres Strait Islander children, which continues today—have disrupted this foundation, leading to compounding cycles of intergenerational and complex trauma. The enduring impact of intergenerational and complex trauma is exemplified in increasing proportions of Aboriginal and Torres Strait Islander children being removed from their families and involved in the child protection and youth justice system—which represents a national crisis. Despite this crisis, the national response remains insufficient. To address these urgent issues, over 200 predominantly Aboriginal and Torres Strait Islander stakeholders, participated in Gathering the Seeds Symposium, the inaugural meeting for the Replanting the Birthing Trees project held in Perth in April 2023. This meeting marked the beginning of a public dialogue aimed at Closing the Gap by advancing community-led strategies to break cycles of trauma and foster cycles of nurturing, recovery, and wellbeing for Aboriginal and Torres Strait Islander parents and children across the first 2000 days. We outline critical shortcomings in the current child protection and youth justice systems, and the urgent need for child wellbeing reform. Importantly we highlight recommendations made in submissions in 2023 to two key Australian inquiries—the National Early Years Strategy and the Human Rights Commission inquiry into out of home care and youth justice systems. We argue that structural reforms and culturally safe and skillful care for parents experiencing trauma and violence is a serious gap, and a national priority. The first 2000 days represents a critical window of opportunity to transform cycles of trauma into cycles of healing. It is time to ‘replant the birthing trees’ and ensure that all Aboriginal and Torres Strait Islander babies and families can have the best possible start to life through comprehensive models of care grounded in recognition of the right to self-determination and culture.